Evaluating the reality of the training process in accordance with the standard specification (ISO10015:2019): A case study at the Higher Institute for Administrative and Security Development (Journal of Accounting and Financial Studies ( JAFS ), 2025)
The objective of this study is to is to assess the extent to which the Higher Institute for Security and Administrative Development adheres to the requirements specification Indicative (ISO10015:2019) guideline. Where field visits and personal observation were conducted by the researcher to reach scientific and practical results and facts, and the procedures will be known through analyzing and measuring the gaps, which includes analyzing the disparity between the current situation for the circle concerned And the terms of the international standard (ISO10015:2019). To demonstrate and achieve this, the case study approach was adopted using the checklist. As a tool for collecting data and information to measure and know the gaps that were diagnosed, frequencies and averages were calculated The study sample, consisting of (46) sections Managers, their assistants, division directors, unit officials, and some people with experience in training operations, was selected., was selected and the results showed that the application Of international specification (ISO10015:2019) . For the standard Requirements, the percentage of compliance has been achieved (82%), and this percentage indicates that The provisions To the circuit in question of the standard have been application almost completely, but they lack appropriate documentation and there is a gap in the requirements of the standard International Standard (ISO10015:2019), which is estimated at (18%). This gap can be addressed by making continuous improvements, analyzing, evaluating and monitoring training processes and focusing on matters related to documentation.